2022
DOI: 10.1111/caje.12608
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants and exports: Firm‐level evidence from Canada

Abstract: We examine how immigrant employment enhances trade at the firm level using unique administrative matched employer-employee data from Canada. We augment a standard model of firms' export market entry and sales decisions with trade costs that depend on destination-specific immigrant employment at the firm level. We estimate simple structural equations derived from the model that relate destination-specific exporting decisions to immigrant employment. We develop a method to deal with the potential endogeneity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The positive role of migrants on trade has been extensively analyzed by various papers (e.g., Head and Ries, 1998;Rauch, 1999Rauch, , 2001Rauch and Trindade, 2002;Felbermayr and Toubal, 2012). While most of the earlier contributions fail to convincingly assess a causal relation due to endogeneity issues and poor data quality (Felbermayr et al, 2015), recent papers use instrumental variable strategies (Peri and Raquena-Silvente, 2010;Ottaviano et al, 2018;Cardoso and Ramanarayanan, 2019;Marchal and Nedoncelle, 2019;Orefice et al, 2021) or natural experiments (Parsons and Vézina, 2018;Bahar et al, 2022;Olney and Pozzoli, 2021) to assess causality. However, these papers either do not allow to distinguish the skill of the migrant or embed almost exclusively low skilled migrant flows (mostly from developing countries), and we know little about the mechanisms by which foreign workers foster trade.…”
Section: Introductionmentioning
confidence: 99%
“…The positive role of migrants on trade has been extensively analyzed by various papers (e.g., Head and Ries, 1998;Rauch, 1999Rauch, , 2001Rauch and Trindade, 2002;Felbermayr and Toubal, 2012). While most of the earlier contributions fail to convincingly assess a causal relation due to endogeneity issues and poor data quality (Felbermayr et al, 2015), recent papers use instrumental variable strategies (Peri and Raquena-Silvente, 2010;Ottaviano et al, 2018;Cardoso and Ramanarayanan, 2019;Marchal and Nedoncelle, 2019;Orefice et al, 2021) or natural experiments (Parsons and Vézina, 2018;Bahar et al, 2022;Olney and Pozzoli, 2021) to assess causality. However, these papers either do not allow to distinguish the skill of the migrant or embed almost exclusively low skilled migrant flows (mostly from developing countries), and we know little about the mechanisms by which foreign workers foster trade.…”
Section: Introductionmentioning
confidence: 99%
“…Gould (1994) first documented the fact that US states export more to countries from which they have a lot of migrants, and Dunlevy (2006) showed the correlation depends on language proximity and corruption in the destination country. Cardoso and Ramanarayanan (2022) use firm level data to show a similar effect. Ottaviano et al (2018) show that this also holds for exports in services.…”
Section: Introductionmentioning
confidence: 79%
“…Wang and Ruan (2019), Sgrignoli et al (2015), Iranzo and Peri (2009), Lewer and Van den Berg (2009), Lewer (2011), Dunlevy andHutchinson (1999), andGould (1994) found that immigration increased trade between the immigrants' host and origin countries. Cardoso and Ramanarayanan (2022) found that immigrant employment enhances trade at the firm level using employer-employeematched data from Canada. Head and Ries (1998) also found that immigration increased Canadian imports and exports; however, imports increased three times more than exports.…”
Section: Provincementioning
confidence: 99%